2014
DOI: 10.1002/ldr.2270
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up of Sustainable Land Management in the Western People's Republic of China: Evaluation of a 10‐Year Partnership

Abstract: The People's Republic of China‐Global Environment Facility Partnership to Combat Land Degradation in Dryland Ecosystems promotes an integrated ecosystem management (IEM) approach to restore, sustain and enhance the productive capacity of dryland ecosystems. This paper provides an analysis and synthesis of the funding strategies, methods and approaches that have been applied and tested under the Partnership to pilot and scale up IEM and sustainable land management (SLM) practices in the western People's Republi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Comparable examples from other countries show similar results (e.g. Tengberg et al ., ; Marques et al ., ). This is not the case in Iceland.…”
Section: Discussionmentioning
confidence: 97%
“…Comparable examples from other countries show similar results (e.g. Tengberg et al ., ; Marques et al ., ). This is not the case in Iceland.…”
Section: Discussionmentioning
confidence: 97%
“…water availability for crops and grass ' soil moisture ' water infiltration ' crop yields ' farm income Sustainability 2016, 8,177 To upscale SLMs, there must be proper recognition of local tradit experimentation [22], a favorable cost-benefit ratio [23,24], local policy and tenu and a participative approach [22,[26][27][28]. Social involvement must be ensured for of SLM practices to be achieved.…”
Section: Macro-catchment: a Methods Of Harvesting Runoff Water From A mentioning
confidence: 99%
“…Lately WH systems are receiving renewed attention. Morocco [83] experimentation [22], a favorable cost-benefit ratio [23,24], local policy and tenure arrangements [25], and a participative approach [22,[26][27][28]. Social involvement must be ensured for the adoption process of SLM practices to be achieved.…”
Section: Water Managementmentioning
confidence: 99%
“…It is also difficult to reduce pesticide usage if farmers have an economic incentive to use more. Existing study has shown that sustainable land management requires both economic incentives to land users and larger investment themes (Tengberg et al, 2016). To add to the complexity, soil is highly heterogeneous and contaminant concentrations can vary by tens to hundreds of times within the distance of a few meters.…”
Section: Human Behaviour and Public Participationmentioning
confidence: 99%